Pay-performance relationship: An empirical study on employee performance in the context of Nigeria - Ismail, Abdussalaam Iyanda; Abdul Majid, Abdul Halim; Joarder, Mohd-Hasanur Joarder (2015)
With the trend of growing globalization, coupled with the uncertainty that clouds the global economic environment, there emerged the need for organizations to enhance their competitive advantage through improvement in productivity and performances of employees who are equipped with the required skills, knowledge and competencies needed for the execution of organizational strategy and planning (Ismail, 2014; Ismail, Abdul-Halim & Joarder, 2015).Research has demonstrated that organizational survival is contingent upon highly productive employee (e.g. Guerrero & Baraud-Didier, 2004; Way, 2002). Organizations with the ability to foreknow their business needs and their workforce needs -especially for highly productive workforce- will gain the decisive competitive advantage.However, employee performance in Nigeria has become a source of worry to organizations.For instance, poor employee performance has caused a setback to the construction industry.This has consequently affected quality of work, duration of projects and firm’s profits (Abdullahi, Bilau, Enegbuma, Ajagbe & Ali, 2011).In the education sector, prevalent poor academic performance of students in Nigeria has been associated with the poor teachers’ performance (Ofoegbu, 2004).Teachers who were rated as ineffective actually produced students of lower academic ability (Adu & Olatundun, 2007; Akiri & Ugborugbo,2009).Nigeria, the largest economy in the African continent due to its recent rebased Gross domestic product (GDP) (Punch, 2014), is experiencing industrial turbulence due to incessant compensation-related industrial strikes, low employee job satisfaction, low social relationship with co-workers etc. (Ajayi, 2012; Ellis, Chinedu & Evans, 2011; Punch, 2014).Human resource with the skills, experience, and knowledge it possesses add economic value to firms (Riordan, Vandenberg, & Richardson, 2005). Hence, it becomes fundamental to the achievement of organizational goals.Consequently, it becomes imperative for organizations to put in place strategies to enhance the performance of their workers.One major factor discernible from Nigeria’s industrial scenario is that the hindrances to the enhanced employee performance are compensation based. Industrial strikes are largely caused by the agitation for better pay and incentives.Although the bulk of literature seems to accept that performance-based pay has a significant effect on employee performance, some studies have demonstrated little doubt about the relationship.Some studies have reported that performance-based pay is least weakly related to employee performance.Some studies argued that implementation of performance-based pay system is the problem (e.g. Egger-Peitler, Hammer, Chmid & Meyer, 2007; Perry, Engbers, & Jun, 2009).Hence, the findings of the extant research are inconclusive.Research has established pay performance nexus in which the productive workers are paid with high pay wages.This practice is strongly based on the scientific management approach which assumes that financial incentives were a motivating factor that stimulate employee performance.The principles of scientific management approach were based upon a foundation of one-sided development of a fair incentive pay system (Ismail, 2006).On the other hand, financial incentives which, according to administrative management approach, reflect fair representations of employee effort would improve efficiency and productivity if employees perceive fairness in it (Dessler, 2005; Hellriegel & Slocum, 1996).To date, there has been support for both arguments. Scientific management approach has formed the basis for many compensation decisions, with many contemporary organizations tying at least part of an individual’s pay to team, work unit or performance (Henderson, 2006; Locke & Latham, 1990a, 1990b).Notably, a careful observation of compensation-performance nexus reveals that the relationship is indirectly affected by perceptions of distributive justice.Thus, investigating distributive fairness is a useful and appropriate contextual variable for this study. Distributive fairness is an organizational context that can positively or negatively influence that behavior (Janssen, 2000; Moorman, 1991).While a good number of studies and empirical evidences have established the link between, various types of compensation and employee performance (e.g. Agwu, 2013; Ajila & Abiola, 2004; Jalaini, et al., 2013; Mensah & Dogbe, 2011; Sajuyigbe, Bosede, & Adeyemi, 2013), research on the effect of some aspects of compensation such as performance-based pay and organizational benefits on employee performance has eluded the attention of researchers.Also, this kind of research in the context of Nigeria is underscored by the the need to motivate human capital through effective reward system since it has the required skills, knowledge and competencies to execute strategy and planning in the organization (Lawler, 2003), the need to address the defective employee performance caused by compensation-related incessant strikes workers, the need to review poor reward system that gives rise to the nonchalant and lackadaisical attitudes of Nigerian workers (Ajayi, 2012; Atunbi, 2014), and the need to look into how workers can be motivated through pay, bonuses, and other benefits as suggested by Ajayi (2012) and Atunbi (2014).In view of the above background, we aim with this study to answer the following research questions: Does performance-based pay influence employee performance?  Do organizational benefits influence employee performance?  Does distributive fairness mediate the relationships among performance-based pay, organizational benefits and employee performance?This study is exceptional for being among the very few research that actually link both performance based pay and organizational benefits to employee performance with the mediation of distributive fairness.Hence contributing immensely to the enhancement of employee performance and the present body of knowledge on performance-based pay, organizational benefits and employee performance.It would also serve as a useful reference for future and continuing studies.This study could be a useful guide for the policy and decision making as well as for academic resources.